2021
DOI: 10.32923/eedj.v1i1.1791
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Students’ Grammatical Errors in Writing Procedure Texts

Abstract: This study investigated the common types of grammatical errors made by 3rd grade of secondary male and female students at SMP Muhammadiyah Pangkalpinang in writing procedure texts and to find out whether there was any significant difference in the errors committed by the students when grouped according to gender. The researcher specified this study in writing procedure text which focused on their errors. The research method used was quantitative. The samples of this study were 30 students that were taken from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Furthermore, they also had difficulties in grammatical aspect. Grammatical errors are usually found in students' writing, as suggested in a study by Husnayaini (Husnayaini, Rizki, & Savitri, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, they also had difficulties in grammatical aspect. Grammatical errors are usually found in students' writing, as suggested in a study by Husnayaini (Husnayaini, Rizki, & Savitri, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, Afifuddin (2016) researched the students' errors in writing descriptive text in which the objective of the research was to find out the types of grammatical errors made by 25 college students who were taking the course of writing III on descriptive writing. The result of this qualitative research revealed that there were many errors occurred in their descriptive text writing such as verb tense, verb form, subjectverb agreement, plural, possessive inflection, definite article, indefinite article, word order, run-on, and fragment.…”
Section: Introductionmentioning
confidence: 99%